Lateralization of verbal ability in pre-psychotic children. - Leask, S; Crow, T (2005)
Deficits in lateralization have been reported in handedness, language and anatomical asymmetry in schizophrenia, but the relationship between these anomalies has been unclear. Extending earlier work demonstrating that degrees of lateralization are related to verbal ability in the general population, we here investigate the relationship in children who later developed psychosis. Using data from a box-marking test and an index of receptive verbal ability in the UK National Child Development study, we constructed three-dimensional plots of verbal ability in relation to left- and right-hand skill at the age of 11 years, and compared the performance of 34 children who by age 28 had developed schizophrenia and 21 who had developed affective psychosis with 12,782 in the total population. In the total population, verbal skill is decreased in those who are close to the L=R line. Children premorbid for schizophrenia are less lateralized and their verbal skill is lower than predicted by their hand skill, with a similar trend in children premorbid for affective psychosis. Thus pre-psychotic children deviate from the general population in the trajectory of lateralization of words. The findings are consistent with the concept that in psychosis at some critical stage in development there is a failure of lateralization of the components of language.